Activity of pectic enzymes involved in the ripening process of lulo (solanum quitoense lam.) (2011)
In the ripening process of the lulo (Solanum quitoense Lam.) physicochemical changes are produced by pectics enzymes as Polygalacturonase (PG), Pectinesterase (PE) and Pectateliase (PL) that acting on pectics substrates of plant tissue, being responsible of the physiological alteration of cells and tissues that results in the fruit softening and the beginning of the premature senescence period. This research explores the foundations of the softening enzymes behavior of lulo epicarp for the activity measurement of PL, PG and PE of fruit´s epicarp and determining their relationship with the softening process during the ripening and senescence process of fruits through follow up of the enzyme expression, the ripening index and instrumental hardness during the lulo fruit ripening under three storage treatments: 1) Control (18° C, 57 days), 2) Refrigeration (18° C, 1 day; 4° C, 14 days; 18° C, 42 days) and 3) Pre-cooling heat shock (27° C, 1 day; 4° C, 14 days; 18° C, 42 days) found that the enzymes expression and softening is reduced by heat treatment, compared with the control group; however, the cold storage inhibit the fruit softening process but chilling injuries was produced, while heat shock, in addition to inhibiting the enzymes expression, inhibited the fruit softening process and protect against chilling injuries prolonging the shelf life in 10 days, showing that it´s the best post-harvest treatment for this type of fruit.